Characterization of 99mTc-ciprofloxacin radiopharmaceuticals as the infection imaging - Nurlaila Z; T. Hasan Basry; Rukmini Iljas; Mimin R. Suminar (Indonesian Journal of Pharmacy, 2005)
Technetium-99m-ciprofloxacin (99mTc-ciprofloxacin) is used in nuclear medicine for infection diagnoses by imaging method. Since a succesful diagnose is depend on its radiopharmaceutical characters, the several physicochemical and biological characters should be investigated in order to have the expectation diagnose. The radiochemical purity was determined with ascending paper chromatography (Whatman 3MM) using 50 % of acetonitril solution as the solvents. The lipophilicity =(P) of 99mTcciprofloxacin was obtained by determination of octanol-water partition and the plasma binding protein was in-vitro investigated with precipitation method using 5% of trichloro acetic acid solution. The biological activity of antibiotic and microbiological uptake was observed in-vitro using Staphylococcus aureus (S. aureus) and Escherichia coli (E.coli). From the experiment, it was obtained that 99mTc-ciprofloxacin has 98.04 ± 0.51 % of radiochemical purity, the lipophilicity (P) = 0.088 ± 0.003, the human plasma binding protein of 64.20 ± 1.74%. The biological activity of 99mTcciprofloxacin was indentic with ciprofloxacin as the starting material and the maximum uptake by S. aureus and E.coli was 97.30 ± 1.01% and 96.03 ± 2.10%, at one hour incubation, respectively. The stability determination showed that 99mTc-ciprofloxacin was still able to be used until two hours after labelling with radiochemical purity of 97.55 ± 0.24%.Key words :radiopharmaceutical, technetium-99m, ciprofloxacin, in, characterization.